1998
DOI: 10.1006/dbio.1997.8815
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Microtubules in New Membrane Formation during Cytokinesis ofXenopusEmbryos

Abstract: In cleaving Xenopus eggs, exposure to nocodazole or cold shock prevents the addition of new plasma membrane to the cleavage plane and causes furrows to recede, suggesting a specific role for microtubules in cytokinesis. Whole-mount confocal immunocytochemistry reveals a ring of radially arranged, acetylated microtubule bundles at the base of all advancing cleavage furrows, from the first cleavage through the midblastula stage. We hypothesize that this novel microtubular structure is involved in transporting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
103
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 54 publications
17
103
2
Order By: Relevance
“…We therefore also compared the ability of GFP-UtrCH to label F-actin in samples extracted with methanol after an initial aldehyde fixation. Consistent with previous studies [Danilchik et al, 1998] methanol extraction did indeed improve microtubule visualization relative to aldehyde-only fixed samples (Fig. 1b).…”
Section: Utrch-based Probes Faithfully Report the Distribution Of F-asupporting
confidence: 92%
“…We therefore also compared the ability of GFP-UtrCH to label F-actin in samples extracted with methanol after an initial aldehyde fixation. Consistent with previous studies [Danilchik et al, 1998] methanol extraction did indeed improve microtubule visualization relative to aldehyde-only fixed samples (Fig. 1b).…”
Section: Utrch-based Probes Faithfully Report the Distribution Of F-asupporting
confidence: 92%
“…However, we cannot rule out the possibility that this late effect is a secondary consequence of early cellularization defects. We have shown previously that nebel is required for the maturation of a microtubule array at the forming furrow, the furrow microtubule array (FMA; Danilchik et al, 1998;Jesuthasan, 1998), which in turn is required for the exocytosis of intraembryonic membrane vesicles at the furrow during cytokinesis (Pelegri et al, 1999). We have shown that this array is also required for the aggregation of the germ plasm during furrow maturation (Pelegri et al, 1999).…”
Section: Mutations Affecting Cellularizationsupporting
confidence: 41%
“…Rather, the surface area taken up in protrusions probably serves as a sink for excess membrane added along the basolateral surface, helping to regulate its overall expansion during basolateral-surface contact: when the protrusive band is obliterated after cytochalasin B treatment, a massive expansion of exposed new membrane results ( Fig. 7B; see also Bluemink and de Laat, 1973;Drechsel et al, 1996;Danilchik et al, 1998).…”
Section: Al 2000)mentioning
confidence: 99%